2021
DOI: 10.3390/su131810415
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Eye Tracking Study of Usability—Towards Sustainable Web Design

Abstract: Websites are one of the most frequently used communication environments, and creating sustainable web designs should be an objective for all companies. Ensuring high usability is proving to be one of the main contributors to sustainable web design, reducing usage time, eliminating frustration and increasing satisfaction and retention. The present paper studies the usability of different website landing pages, seeking to identify the elements, structures and designs that increase usability. The study analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 119 publications
0
14
0
1
Order By: Relevance
“…89 Hence, UX researchers apply physiological measurements to uncover the true experience of a user employing a product. 90 For instance, eye tracking technology is able to record visual attention 91,92 ; electroencephalography can detect emotional responses [93][94][95] ; galvanic skin response can measure stress and arousal through skin conductivity 96,97 ; and electrocardiogram (ECG) and electromyogram (EMG) can measure stress levels 98,99 and muscle-arousing activities that highlight the difficulties of product use on a cognitive level. 19…”
Section: Ux Research Methodsmentioning
confidence: 99%
“…89 Hence, UX researchers apply physiological measurements to uncover the true experience of a user employing a product. 90 For instance, eye tracking technology is able to record visual attention 91,92 ; electroencephalography can detect emotional responses [93][94][95] ; galvanic skin response can measure stress and arousal through skin conductivity 96,97 ; and electrocardiogram (ECG) and electromyogram (EMG) can measure stress levels 98,99 and muscle-arousing activities that highlight the difficulties of product use on a cognitive level. 19…”
Section: Ux Research Methodsmentioning
confidence: 99%
“…Obtaining clear and objective information should be the basis for any marketing research. The emergence of consumer neuroscience as an extremely valuable part of marketing research has prompted restrictions on traditional research techniques aimed at self-assessment [34,35]. The main weakness of traditional research techniques is that they are only able to capture conscious reactions and customer decisions, while neuroimaging techniques offer objective measurements of nerve processes that appear in the process of decision-making itself [36].…”
Section: Consumer Neurosciencementioning
confidence: 99%
“…Experiments show that the quality-function deployment method and house of quality tools of the model can promote the development of new business cooperation between small-and medium-sized enterprises (SMEs) [4]. Ichindelean et al explored the elements, structure, and design to improve the usability of web pages based on eye tracking technology and found that the center and right side of web pages were the most concerned according to the feedback of eyeball instrument, fixation position, sequence and duration, and saccade and revisit of the same elements [5]. Marco et al designed a web-based application to predict probe binding specificity from genome-scale sequence alignment information by using supervised machine learning.…”
Section: Related Workmentioning
confidence: 99%